Situational analysis of the hotel sector in the face of the emergence of platforms digital hosting. Case: Riobamba-Ecuador - Carrasco Sanunga, Lourdes; Loor Bravo, Lucia (mktDESCUBRE; Vol 1 No 22 (2023): Twenty-second Edition (July - December)DO - 10.36779/mktdescubre.v1i22.840, 2023)
The research analyzes the economic impact of digital lodging platforms on the hotel sector in Riobamba, Ecuador, within the context of the sharing economy. Through a mixed approach, it examines technological transformation and its influence on the hospitality industry, with an emphasis on the dynamics introduced by platforms like Airbnb. It highlights how these have modified competition and lodging preferences, challenging traditional models, especially in the face of the COVID-19 pandemic scenario, which exacerbated the sector’s challenges with a notable decrease in occupancy and the temporary closure of establishments. Nevertheless, a resilience capacity is observed in some businesses in Riobamba. Using surveys, a lack of awareness of the term P2P commerce but an extended use of sharing economy platforms is revealed, affecting consumer choices and fostering renewed competition in the sector. The data indicate a slight decrease in the offer of traditional accommodation since the rise of Airbnb in 2018, positioning Riobamba as a relevant destination for P2P lodging. The conclusion underscores the need for strategic adaptation of hotels to the new market realities, driven by technology and changing consumer preferences, to promote economic growth and sustainability.